Contribution of Principal and Supervision on the Performance of Teacher Motivation Smkn 1 Palembayan - Delfauzul Delfauzul; Wakhinuddin Simatupang; Hasan Maksum (International Journal of Educational Dynamics, 2021)
Based on the initial survey in the field, the performance of the teachers of SMKN 1 Palembanyan seems still low, it is estimated that low teacher performance is caused by low teacher work motivation and lack of implementation of school principal supervision. This quantitative research aims to reveal the contribution of principal supervision and work motivation to the performance of teachers of SMKN Palembayan. The hypotheses proposed in this study are 3 hypotheses 1) the supervision of the principal takes effect on teacher performance; 2) Work motivation takes effect on teacher performance, and 3) Principal supervision and work motivation together contribute to teacher performance. The population of this study were all 37 teachers of SMKN 1 Palembanyan, so the sample in this study amounted to 28 teachers, not including the principal, the vice principal because the principal, and the deputy principal were the people who acted as supervisors. While the research data was collected through a questionnaire in the form of a Likert scale after being tested for validity and reliability. Based on the analysis of the research data, it was revealed that the supervision of the principal made a significant influence on teacher performance by 36,4% and work motivation made a significant influence on teacher performance by 24,7%. Together, principal supervision and work motivation influence 37.0% of teacher performance, and the remaining 63.0% was determined by other variables. Based on the findings of this study, it can be concluded that the two independent variables, namely the supervision of the principal and work motivation, play a very important role in improving teacher performance, in addition to other variables not examined in this study.